PENGARUH BUKU AJAR KIMIA ELEKTRONIK BERBASIS BUDAYA LOKAL BALI TERHADAP HASIL BELAJAR SISWA SMA - Putu Nindya Sri Satya Lestari; I Wayan Redhana; I Wayan Subagia (Postgraduate, University of Mataram, 2022)
Student learning outcomes are still relatively low, this is due to the lack of utilization of local wisdom-based electronic textbooks in class by teachers. The application of Balinese local culture-based electronic textbooks is believed to be able to improve learning outcomes. The purpose of this study was to describe and explain whether or not there were differences in learning outcomes between students who took the pretest and students who did not take the pretest and to describe and explain whether or not there were differences in learning outcomes between students who studied using chemistry textbooks based on local Balinese culture and students who studied using conventional books. The design of this study uses the Solomon four-group design. The research location was carried out at SMAN 5 Denpasar with a research sample of class XI MIPA. The instrument in this study consisted of a learning achievement test using a dichotomous scale. The research data were analyzed using a two-way analysis of variance test. The research results obtained were that there were no differences in learning outcomes between students who were given a pretest and students who were not given a pretest and there were differences in learning outcomes between students who studied using electronic chemistry textbooks based on local Balinese culture and students who studied using conventional textbooks